2002
DOI: 10.1097/00004647-200202000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways of Protein Synthesis Inhibition during Brain Reperfusion: Implications for Neuronal Survival or Death

Abstract: Protein synthesis inhibition occurs in neurons immediately on reperfusion after ischemia and involves at least alterations in eukaryotic initiation factors 2 (eIF2) and 4 (eIF4). Phosphorylation of the alpha subunit of eIF2 [eIF2(alphaP)] by the endoplasmic reticulum transmembrane eIF2alpha kinase PERK occurs immediately on reperfusion and inhibits translation initiation. PERK activation, along with depletion of endoplasmic reticulum Ca2+ and inhibition of the endoplasmic reticulum Ca2+ -ATPase, SERCA2b, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
171
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 140 publications
(209 reference statements)
7
171
0
1
Order By: Relevance
“…Phosphorylation of PERK and eIF2␣ and reduction in protein synthesis during ischemia-reperfusion in GECs are in keeping with the up-regulation of bip and grp94 expression demonstrated previously (10). Similar to complement, eIF2␣ phosphorylation occurred early, whereas bip and grp94 expression was evident at 24 h. Our results in GECs are in keeping with previous studies (41)(42)(43), which showed that PERK and eIF2␣ became phosphorylated after experimental brain ischemia. However, unlike GECs, another study reported that brain ischemia is associated with activation of cPLA 2 (44).…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorylation of PERK and eIF2␣ and reduction in protein synthesis during ischemia-reperfusion in GECs are in keeping with the up-regulation of bip and grp94 expression demonstrated previously (10). Similar to complement, eIF2␣ phosphorylation occurred early, whereas bip and grp94 expression was evident at 24 h. Our results in GECs are in keeping with previous studies (41)(42)(43), which showed that PERK and eIF2␣ became phosphorylated after experimental brain ischemia. However, unlike GECs, another study reported that brain ischemia is associated with activation of cPLA 2 (44).…”
Section: Discussionsupporting
confidence: 92%
“…Agents that inhibit eIF2␣ phosphorylation could promote survival under desired conditions, for example to inhibit macrophage apoptosis upon viral infection (9) or prevent ischemic cell injury (71). Alternatively, direct targeting of therapeutic agents to induce eIF2␣ phosphorylation may accentuate apoptosis of virus-infected cells (72).…”
Section: Discussionmentioning
confidence: 99%
“…12 In brain ischemia, neuronal cells cannot receive sufficient glucose and oxygen required for modification of proteins in ER, and ER stress may occur. 23 The induction of CHOP mRNA by brain ischemia or hypoxia has been reported. [24][25][26][27] However, the exact role of CHOP in ER stress-mediated neuronal apoptosis in brain ischemia or hypoxia remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%